ChemInform Abstract: Protection of a New Heptapeptide from Carapax trionycis Against Carbon Tetrachloride‐Induced Acute Liver Injury in Mice. Issue 19 (13th May 2014) - Wang, Penglong; Zhang, Yuzhong; An, Yawen; Xu, Kuo; Xu, Xin; Fu, Chao; Lin, Jinxuan; Xu, Shixun; Li, Qiang; Lei, Haimin
Abstract The new heptapeptide GAGPHGG (OC1) (I) is isolated from Carapax trionycis.